2022
DOI: 10.1007/s11547-022-01545-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of diffuse idiopathic skeletal hyperostosis (DISH) in Italy

Abstract: Purpose Diffuse idiopathic skeletal hyperostosis (DISH) is a benign condition characterized by ossification of the spine and prominent enthesopathies. Highly heterogeneous epidemiological figures have been reported in the literature, while in Italy the largest study has been conducted in 1992. The aim of our research is to contribute updated information about prevalence of DISH in Italy and to describe the clinical and radiographic characteristics associated with the disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…4,5 Literature has also found that males have a higher prevalence of DISH. 8,[11][12][13] This study found that patients with DISH had a higher prevalence of diabetes mellitus, congestive heart failure, and dementia. Previous studies have also shown higher prevalence of DISH in patients with DM.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…4,5 Literature has also found that males have a higher prevalence of DISH. 8,[11][12][13] This study found that patients with DISH had a higher prevalence of diabetes mellitus, congestive heart failure, and dementia. Previous studies have also shown higher prevalence of DISH in patients with DM.…”
Section: Resultsmentioning
confidence: 66%
“…Previous literature has found the average at which DISH was diagnosed was between 57 years old and 68 years old, similar to but slightly younger than the mean age shown in the present study's DISH cohort. [6][7][8]12 There is an increased prevalence of DISH at older ages. 4,5 Literature has also found that males have a higher prevalence of DISH.…”
Section: Resultsmentioning
confidence: 99%
“…DISH primarily affects older individuals, while axSpA affects a younger population. DISH has a prevalence ranging from 3.8% [6] to 30% [7][8][9][10][11][12][13][14][15] in people aged > 50 years. The prevalence of DISH is increasing with age [16].…”
Section: Similarities and Differences In Epidemiology And Demographicsmentioning
confidence: 99%